Karakteropvoeding in Suid-Afrikaanse skole - Klerk, J. de (Koers, 2005)
Character education in South African schools The success of a democratic society as well as effective teaching and learning presupposes virtuous people who live according to certain core values. This article focuses from a Christian perspective on character education, one of the approaches by which values can be established in South African schools. The proponents of character education accept the existence of certain core ethical values. Parents, schools and communities can work together to help children understand these values, care about them and try to live accordingly. The various methods employed by this approach to instill values in schools are discussed critically. The specific problems which the complex pluralistic South African society presents to this comprehensive approach to the instilling of values are also discussed. The critics of this approach warn against the possibility of hidden dangers of rigidity, moralising, manipulation and indoctrination which are all contraproductive to moral development. From a Biblical-educational point of view this approach can successfully be used to instill core Biblical values, on condition that it is accompanied by credible adult role models and that due consideration is given to the uniqueness of the individuals involved. Character-education, if applied with awareness of the comprehensiveness of the approach and sensitivity to the multi-cultural situation, has the potential to address the moral dilemmas in South African schools.